Maternal genetic origin of the late and final Neolithic human populations from present‐day Poland. Issue 2 (26th July 2021) - Juras, Anna; Ehler, Edvard; Chyleński, Maciej; Pospieszny, Łukasz; Spinek, Anna Elżbieta; Malmström, Helena; Krzewińska, Maja; Szostek, Krzysztof; Pasterkiewicz, Wojciech; Florek, Marek; Wilk, Stanisław; Mnich, Barbara; et al.
Abstract: Objective: We aim to identify maternal genetic affinities between the Middle to Final Neolithic (3850–2300 BC) populations from present‐day Poland and possible genetic influences from the Pontic steppe. Materials and methods: We conducted ancient DNA studies from populations associated with Złota, Globular Amphora, Funnel Beaker, and Corded Ware cultures (CWC). We sequenced genomic libraries on Illumina platform to generate 86 complete ancient mitochondrial genomes. Some of the samples were enriched for mitochondrial DNA using hybridization capture. Results: The maternal genetic composition found in Złota‐associated individuals resembled that found in people associated with the Globular Amphora culture which indicates that both groups likely originated from the same maternal genetic background. Further, these two groups were closely related to the Funnel Beaker culture‐associated population. None of these groups shared a close affinity to CWC‐associated people. Haplogroup U4 was present only in the CWC group and absent in Złota group, Globular Amphora, and Funnel Beaker cultures. Discussion: The prevalence of mitochondrial haplogroups of Neolithic farmer origin identified in Early, Middle and Late Neolithic populations suggests a genetic continuity of these maternal lineages in the studied area. Although overlapping in time – and to some extent – in cultural expressions, none of the studied groups (Złota, Globular Amphora, Funnel Beaker), shared a close genetic affinity to CWC‐associated people, indicating a larger extent of cultural influence from the Pontic steppe than genetic exchange. The higher frequency of haplogroup U5b found in populations associated with Funnel Beaker, Globular Amphora, and Złota cultures suggest a gradual maternal genetic influx from Mesolithic hunter‐gatherers. Moreover, presence of haplogroup U4 in Corded Ware groups is most likely associated with the migrations from the Pontic steppe at the end of the Neolithic and supports the observed genetic distances. Abstract :